Stable water-in-oil emulsions formulated with polyglycerol polyricinoleate and glucono-δ-lactone-induced casein gels. (June 2016) - Wang, Pengjie; Cui, Na; Luo, Jie; Zhang, Hao; Guo, Huiyuan; Wen, Pengcheng; Ren, Fazheng
Abstract: The destabilization of water-in-oil (W/O) emulsions greatly restricts their application. Converting the inner water droplets into soft solid-like gelled particles is an appealing strategy to improve the stability of W/O emulsions. In the present communication, we propose a novel method for preparing stable W/O emulsions containing gelled water droplets. In this method, the 3% (w/v) casein dispersions containing 0.9% (w/v) glucono-δ-lactone (GDL) and soybean oil with 2% or 6% lipophilic emulsifier polyglycerol polyricinoleate (PGPR) were homogenized to form W/O emulsions. Three hours later, the GDL-induced gelation of caseins in the inner aqueous phase occurred; thus, the W/O emulsions containing gelled water droplets were formed. The stability of the emulsions was characterized by Turbiscan analysis, particle size changes and visual inspection of phase separation. It was found that the W/O emulsions containing GDL-induced casein gels in the inner aqueous phase showed higher resistance to destabilization than the non-gelled W/O emulsions. In addition, the stability of the emulsions formulated by the gelled aqueous phase and 2% PGPR was even higher than emulsions with 6% PGPR in the absence of the gelled aqueous phase. These findings suggested that this method is an effective strategy for improving the long-term stability of W/O emulsions. Graphical abstract: Highlights: W/O emulsions containing gelled water droplets were prepared. The gelled water droplets were induced by glucono-δ-lactone, without harsh treatments. The stability of W/O emulsions formulated with gels was significantly improved.